(untitled) (Conferencea, 2023)
The article analyzes the philosophical problems of artificial intelligence, the role of artificial intelligence, information, information and information technologies in the development of society, the analysis of information as a mechanism of social development, the solution of existing problems and future tasks in this field is presented.